Apoptosis and upregulation of TNF-α and TRAIL receptor 1 (DR4) in the pathogenesis of food protein-induced enterocolitis syndrome - Jin-Bok Hwang; Sang Pyo Kim; Yu Na Kang; Seong-Ryong Lee; Seong-Il Suh; Taeg Kyu Kwon (Korean Pediatric Society, 2010)
Purpose : Expression levels of tumor necrosis factor (TNF)-?#6181;xpression on the mucosa of the small intestine is increased in patients with villous atrophy in food protein-induced enterocolitis syndrome (FPIES). TNF-?#6184;as been reported to induce apoptotic cell death in the epithelial cells. We studied the TNF family and TNF-receptor family apoptosis on the duodenal mucosa to investigate their roles in the pathogenesis of FPIES. Methods : Fifteen infants diagnosed as having FPIES using standard oral challenge test and 5 controls were included. Terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) staining was performed to identify the apoptotic cell death bodies. Immunohistochemical staining of TNF-?#6944;Fas ligand (FasL) for TNF family and TNF-related apoptosis-including ligand (TRAIL) receptor 1 (DR4), TRAIL receptor 2 (DR5), and Fas for TNF-receptor family were performed to determine the apoptotic mechanisms. Results : TUNEL+ was significantly more highly expressed in the duodenal mucosa of FPIES patients than in controls (P = 0.043). TNF-?#6184;P =0.0001) and DR4 (P =0.003) were significantly more highly expressed in FPIES patients than in controls. Expression levels of FasL, Fas, and DR5 were low in both groups and were not significantly different between the 2 groups. Conclusion : These results suggest that FPIES pathogenesis is induced by apoptosis, and that TNF-?#6181;xpression and DR4 pathway may have an important role in apoptosis.